2017
DOI: 10.1111/1467-6427.12153
|View full text |Cite
|
Sign up to set email alerts
|

Inequity of sacrifice and marital satisfaction in Chinese young couples

Abstract: There is an emerging body of research focusing on the positive and negative effects of sacrifice on relationship quality, but few of them have investigated the effects of the inequity of sacrifice. In the light of social exchange theory and equity theory, this study examines the roles inequity of sacrifice plays in marital satisfaction in China. Based on the questionnaires completed by 115 Chinese young couples, we find that wives' perceived inequity of sacrifice, rather than husbands' perceived inequity or th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 63 publications
1
20
0
Order By: Relevance
“…Thus, both individuals should achieve better long-term outcomes if, in repeated interactions, they favor prosocial responses over self-interested ones (Pruitt & Kimmel, 1977). Some empirical research has indeed corroborated these ideas by showing positive associations between sacrifice and relationship functioning (e.g., higher relationship satisfaction, commitment, dyadic coping; e.g., Chen & Li, 2007; Lan et al, 2017; Ruppel & Curran, 2012; Van Lange, Rusbult, et al, 1997; Wieselquist et al, 1999; Zhang & Li, 2015).…”
Section: Sacrifice and Personal And Relationship Well-being: Two Diff...mentioning
confidence: 91%
“…Thus, both individuals should achieve better long-term outcomes if, in repeated interactions, they favor prosocial responses over self-interested ones (Pruitt & Kimmel, 1977). Some empirical research has indeed corroborated these ideas by showing positive associations between sacrifice and relationship functioning (e.g., higher relationship satisfaction, commitment, dyadic coping; e.g., Chen & Li, 2007; Lan et al, 2017; Ruppel & Curran, 2012; Van Lange, Rusbult, et al, 1997; Wieselquist et al, 1999; Zhang & Li, 2015).…”
Section: Sacrifice and Personal And Relationship Well-being: Two Diff...mentioning
confidence: 91%
“…Research examining the link between actual performed sacrifices and personal and relationship well-being has not yielded consistent results. Some studies found that sacrifice was positively associated with well-being (e.g., Chen & Li, 2007; Lan et al, 2017; Ruppel & Curran, 2012), whereas others documented that sacrifice was negatively related to well-being (e.g., Totenhagen & Curran, 2011; Whitton et al, 2007; Young & Curran, 2016). Others still found no association between the two (e.g., Impett, Gable, & Peplau, 2005; Righetti, Gere, Hofmann, Visserman, & Van Lange, 2016; Totenhagen, Curran, Serido, & Butler, 2013), a finding that is consistent with preliminary results from a recent meta-analysis of the link between actual performed sacrifice and relationship well-being (Righetti et al, 2019).…”
Section: Sacrifice and Personal And Relationship Well-beingmentioning
confidence: 99%
“…Given previous research demonstrating that gratitude expressions can elicit negative responses (e.g., by signaling interpersonal distance; Zhang et al, 2018), we also left open the possibility that either of these ways of expressing gratitude may backfire. For example, although romantic partners typically idealize non-contingent giving and receiving with no expectation for immediate reciprocation (Clark et al, 2010), empirical findings have shown that a sense of equity in relationships is also important, and that inequity in the direction of underbenefiting (i.e., feeling as though one receives fewer benefits from the relationship than their partner) can be particularly detrimental for the person’s relationship quality (Lan et al, 2017; Sprecher, 2018). As such, if responsiveness- or cost-highlighting gratitude expressions instill a sense that the benefactor is being underbenefitted, it is possible that either could cause discomfort and conflicting feelings about the relationship for the benefactor.…”
mentioning
confidence: 99%